Fiscal culture and its relationship with entrepreneurs’ compliance with tax responsibilities in a market of Trujillo, 2023 - Sánchez Baca, Cristina Beatriz; Rodríguez Abraham, Antonio Rafael; Araujo Calderón, Wilder Adalberto; García Juárez, Hugo Daniel; Cruz Salinas, Luis Edgardo (LACCEI, 2024)
The purpose of this study was to determine the impact of tax culture on compliance with tax responsibilities of entrepreneurs in a market in Trujillo, 2023. Regarding the methodology, the research adopted a quantitative, applied approach, and the design was non-experimental, correlational, and cross-sectional. The sample was made up of 212 entrepreneurs from a market in Trujillo, who responded to data collection instruments, such as the questionnaire and documentary analysis.The obtained results show that 89.60% of entrepreneurs have a medium-low level of tax culture, and 64.60% of entrepreneurs have a low level of compliance with tax responsibilities. Tax culture and compliance with tax responsibilities among entrepreneurs in a market have a significant positive correlation of 0.217, with a significance level of 0.002. The relationship is weakly positive, and it is concluded that if fiscal culture increases, so does the compliance with tax responsibilities.